Settlement response of a reinforced shallow earth bed - Ghosh C.; Madhav M.R. (My University, 2025)
Presently, reinforcement in the form of extensible (e.g. geosynthetics) or apparently inextensible (e.g. metallic strips) inclusions are applied widely for strengthening shallow foundation beds. The effective use of reinforcement requires the understanding of its performance in combination with the strength characteristics of the soil to be reinforced. This paper is concerned with the development of a simple mathematical model to account for the membrane effect of a reinforcement layer on the load-settlement response of a reinforced granular fill-soft soil foundation system. The nonlinear loading pressure-settlement response of the granular fill and soft soil, respectively, for plane strain loading condition are incorporated into the formulation. Parametric studies for a uniformly loaded strip footing show that membrane action of reinforcement causes reduction in the settlement below the footing which is over and above the effect of granular fill. © 1994.